Influence of Fertilization System on Wheat Yields in Terms of Global Climate Change - Jelić, Miroslav; Nikolić, Olivera; Knezevic, D.; Savic, Nadica; Dugalić, G. (Journal of Economic Development, Environment and People, 2013)
Over the last few decades, wheat production, both in Serbia and worldwide, has been practiced under characteristic agrometeorological conditions. It has generally been affected by specific strongly marked agrometeorological and climate extremes, most notably extreme temperature and drought events during critical periods in the growing season, which mostly had a negative impact on the growth, development and yield of wheat in Central Serbia. This paper presents results and discussion on both the potential effect of climate change on winter wheat yield and the possibility to alleviate it through an appropriately adjusted fertilization system. The present study on the effect of different rates and ratios of NPK fertilizers on grain yield in seven winter wheat cultivars under different (dry and “normal“) conditions during the year was conducted in a long-term field experiment at the Small Grains Research Centre in Kragujevac over a period of seven years (2000/01-2006/07). Depending on the fertilization treatment, the average yield reduction in dry years showed 50% variation relative to “normal” years. The highest reduction in grain yield and other productive traits of wheat in dry years was observed in the treatment involving nitrogen nutrition, particularly lower application rates. As compared to the non-treated control, the use of complete NPK fertilization having an increased amount of phosphorus resulted in the lowest yield reduction during the dry years that were unfavorable for winter wheat production. The average grain yield reduction in dry years was lowest in wheat cultivar Matica and highest in Kg-100, respectively.